Poligami dalam Islam dan Keadilan Gender - Zainal Abidin; Muhammad Safuan; Rafiqul Huda Siregar (The International Journal of Pegon : Islam Nusantara civilization, 2022)
This article traces the thoughts of two Indonesian gender activists, Mansour Fakih and Faqihuddin Abdul Kodir regarding polygamy and gender justice. Through a qualitative approach and literature study, this paper discusses common opinions about polygamy to focus on the opinions of both of them. In general, polygamy is allowed if it is able to do justice and for the benefit. This opinion was deemed incorrect by two thinkers and activists from Indonesia, Mansour Fakih through his gender analysis and social transformation tools had aspirations so that gender justice could be realized, one of which was by interpreting religious texts. It was this interpretation of religious texts that was later continued by Faqihuddin Abdul Kodir, whom he popularized with the term Qiraah Mubadalah. From the methodological device he initiated, it was concluded that polygamy was judged to be less maslahah and more maslahah monogamous. Artikel ini menelusuri pemikiran dua tokoh aktivis gender Indonesia, Mansour Fakih dan Faqihuddin Abdul Kodir terkait poligami dan keadilan gender. Melalui pendekatan kualitatif dan studi kepustakaan, karya tulis ini mendiskusikan pendapat umum mengenai poligami hingga fokus pada pendapat mereka berdua. Secara umum poligami diperbolehkan jika mampu berlaku adil serta untuk kemaslahatan. Pendapat ini dirasa kurang tepat oleh dua pemikir sekaligus aktivis dari Indonesia, Mansour Fakih melalui perangkat analisis gender dan transfromasi sosialnya memiliki cita-cita agar keadilan gender bisa terwujud, salah satunya dengan penafsiran teks agama. Penafsiran teks agama inilah yang kemudian dilanjutkan oleh Faqihuddin Abdul Kodir, yang ia populerkan dengan istilah Qiraah Mubadalah. Dari perangkat metodologis yang ia gagas itu, disimpulkan bahwa poligami dinilai kurang maslahah dan lebih maslahah monogami.